Identification and validation of a prognostic model based on ferroptosis-associated genes in head and neck squamous cancer - Wei, Ming; Tian, Yongquan; Lv, Yunxia; Liu, Guancheng; Cai, Gengming (Frontiers in Genetics, 2022)
Ferroptosis is that under the action of ferrous iron or ester oxygenase, unsaturated fatty acids highly expressed on the cell membrane are catalyzed to undergo lipid peroxidation, thereby inducing cell death. In this study, we used ferroptosis marker genes to identify 3 stable molecular subtypes (C1, C2, C3) with distinct prognostic, mutational, and immune signatures by consensus clustering; TP53, CDKN2A, etc. Have higher mutation frequencies in the three subtypes. C3 has a better prognosis, while the C1 subtype has a worse prognosis. WGCNA is used to identify molecular subtype-related gene modules.After filting, we obtained a total of 540 genes related to the module feature vector (correlation>0.7).We performed univariate COX regression analysis on these genes, and identified a total of 97 genes (p < 0.05) that had a greater impact on prognosis, including 8 ‘‘Risk” and 89 ‘‘Protective” genes. After using lasso regression, we identified 8 genes (ZNF566, ZNF541, TMEM150C, PPAN, PGLYRP4, ENDOU, RPL23 and MALSU1) as ferroptosis-related genes affecting prognosis. The ferroptosis prognosis-related risk score (FPRS) was calculated for each sample in TCGA-HNSC dataset. The results showed that FPRS was negatively correlated with prognosis.The activated pathways in the PFRS-high group mainly include immune-related pathways and invasion-related pathways. We assessed the extent of immune cell infiltration in patients in our TCGA-HNSC cohort by using the expression levels of gene markers in immune cells. The FPRS-high group had a higher level of immune cell infiltration. We found that the expression of immune checkpoints was significantly up-regulated in the FPRS-low group and the FPRS-high group had a higher probability of immune escape and a lower probability of benefiting from immunotherapy. In this work, we constructed a scoring Ferroptosis-related prognostic model that can well reflect risk and positive factors for prognosis in patients with head and neck squamous cell carcinoma. It can be used to guide individualized adjuvant therapy and chemotherapy for patients with head and neck cancer. Therefore, it has a good survival prediction ability and provides an important reference for clinical treatment.